Molecular aspects of distal kidney tubular acidosis in children, its long-term outcome, and relationship with hyperammonemia - GÖKCE, İBRAHİM; ATA, PINAR; YILDIZ, NURDAN (My University, 2022)
Objective: We aimed to present the characteristics, genetic analysis results, long-term prognosis of our patients with distal kidney tubular acidosis, and the relationship between hyperammonemia and distal kidney tubular acidosis. Materials and Methods: Biochemical, clinical, and imaging findings were collected at presentation and the last clinic visit, and results of the genetic analysis were recorded. Results: Our study included 9 patients (3 female, 33%). The median age at diagnosis was 3 months, and the median follow-up period was 111 months. Height standard deviation scores were less than −2 in 4 (44%) patients at presentation and in 3 (33%) at the last clinic visit. The median estimated glomerular filtration rate was 98 mL/min/1.73 m2 at presentation and 126 mL/min/1.73 m2 at the last clinic visit. We have found 8 different types of mutations of 2 genes, including 6 in the ATP6V0A4 gene, 2 in the SLCA4A1 gene, and 2 of them were novel. At the time of presentation, nephrocalcinosis and hypercalciuria were present in all our patients, but at the last visit, only 1 patient had hypercalciuria. Sensorineural hearing loss was found in 4 of our patients with a mutation in the ATP6V0A4 gene. Serum ammonia levels were found to be high in 3 patients with mutations in the ATP6V0A4 gene. Conclusion: Adequate metabolic control is essential for optimal growth and preserved kidney function in distal kidney tubular acidosis patients. Distal kidney tubular acidosis may be associated with hyperammonemia. We recommend keeping potassium levels at high-normal levels to reduce ammonia levels, especially in the absence of acidosis.
Keywords: Tıp; Dahili Tıp Bilimleri; Çocuk Sağlığı ve Hastalıkları; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Child Health and Diseases; Health Sciences; PEDİATRİ; Klinik Tıp; Klinik Tıp (MED); PEDIATRICS; CLINICAL MEDICINE; Clinical Medicine (MED); Pediatri; Pediatri, Perinatoloji ve Çocuk Sağlığı; Pediatrics; Pediatrics, Perinatology and Child Health; Distal kidney tubular acidosis; genetics; children; hyperammonemia; SENSORINEURAL HEARING-LOSS; ATP6B1 GENE; MUTATIONS; ATP6V0A4; DEAFNESS; SUBUNIT; BAND-3; Distal kidney tubular acidosis; genetics; children; hyperammonemia